Pemanfaatan Limbah Jerami Padi sebagai Bahan Utama Pembuatan Sanggul Fantasi - Atik Lestari; Sofia Daniati; Nurulisma Saputri (Garina, 2025)
This study is an experimental research with a descriptive qualitative approach aimed at developing innovative hair styling in the form of fantasy buns made from rice straw waste as an environmentally friendly creative expression. The research was conducted through direct experimentation in creating fantasy hair buns using rice straw, followed by product feasibility and aesthetic assessments. The feasibility test was carried out by expert validators using the expert judgement method, while a public test was conducted to measure the level of interest and acceptance of the community through questionnaires distributed via Google Form. The results indicate that rice straw is suitable as an alternative material for creating fantasy hair buns due to its strong texture, easy shaping properties, and the ability to produce unique and artistic visual effects. These findings are expected to contribute to the utilization of agricultural waste into creative and valuable products in the field of hair styling.